Różnorodność kultur i stylów w doświadczeniu emigracyjnym Emila Ciorana i Czesława Miłosza - Szczepankowska, Irena (Stylistyka, 2019)
The aim of this paper is to confront the reflections of two famous personages, whose lives and writing activities were developing almost simultaneously over the last century: Emil Cioran (1911–1995), a Romanian philosopher and essayist, and Czesław Miłosz (1911–2004), a Polish poet. The worldview and artistic choices made by both writers in the mature phase of their lives differ significantly, yet what they have in common is experiencing various cultures, first in their homelands in Central and Eastern Europe, and later abroad – in Western countries (France and the USA). These experiences triggered the deep awareness of the relation between the communication style in various areas of the human activity and the culture of a given society, which is shaped by the history and geography and which manifests itself in language and numerous traditional rituals of the community and behaviours of its representatives. Cioran identifies the cultural style with the “good taste” rule system developed by the community, or in fact its model-setting elite. The choice of language and style involves not only specific artistic decisions but also, which is more significant and compliant with the idea of style as a way of thought and action, and not only expression, it is linked to the worldview, which is inscribed in the language code. In his wish to acquire the “French style”, the author of Le Style comme aventure did his best to “lose his memory”: he even forgot how to speak the Romanian language. It is in the tension between the consciously practised French style and the mentality shaped in different cultural conditions that the writer achieves the longed-for distance, which is the essence of art and, in a sense, a privilege of the emigrant status also for Czesław Miłosz. In his collection of essays titled Szukanie ojczyzny, Miłosz emphasises, however, that the “loss of memory” is neither possible nor necessary for achieving such a distance. On the contrary, preserving a relation with the cultural heritage of the environment and epoch in which one was raised is the basis for becoming accustomed with the place of exile and at the same time observing it from a distance. This relation, which manifests itself primarily in the poet’s preserving his “mother tongue” as the language of his literary work, by no means implies artistic determination: Stylistic conventions are, according to the Polish poet, more permanent than the cultural worlds and constitute a space for are lative freedom of choice.